Influence Of Calcium On Water Relation Of Two Cultivars Of Wheat Under Salt Stress - Akhter, Nahid; Hossainn, F; Karim, A (International Journal of Environment, 2013)
The purpose of the present investigation was to study the effects of Ca2+ on water relation of two wheat cultivars (Akbar and Kanchan) under salt stress. The two wheat cultivars were grown in pots with 0 and 150 mM NaCl salinity. Calcium was applied in the form of gypsum in 0.12, 0.24 and 0.36g pot-1 (that is 20, 40 and 60 kg ha-1) respectively. Salinity decreased RWC, WRC, exudation rate and ψleaf, while increased WSD and WUC. Application of increased levels of Ca improved the plant water status in both cultivars. The results obtained in the present study suggest that elevated Ca2+ increases salt tolerance by improving the plant water status. International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 1-8 DOI: http://dx.doi.org/10.3126/ije.v2i1.9202